ANALISIS KINERJA PENDAPATAN ASLI DAERAH YANG DIKAITKAN DENGAN BELANJA DAERAH PADA PEMERINTAHAN KOTA BAUBAU TAHUN ANGGARAN 2017-2021 - Abdullah, Rudi (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2022)
The purpose of this study is to measure the performance of local revenue (PAD) which is associated with the regional expenditure gang of the Baubau City government based on the results of the calculation of the independence ratio, effectiveness ratio, compatibility ratio, and efficiency ratio, during the 2017-2021 fiscal year. quantitative data, quantitative data is data that is measured on a numerical scale, quantitative data in this study is a report on the realization of the Baubau City APBD for the 2017-2021 fiscal year. The data from this study is based on secondary data sources, secondary data is a source of research data obtained through intermediary media or through indirectly in the form of books, records, existing evidence or archives that have been published in general, in this study secondary data in the form of data (PAD) and regional expenditures. The analytical method used is descriptive analysis method using financial ratio analysis.